2020
DOI: 10.1007/s10257-020-00472-6
|View full text |Cite
|
Sign up to set email alerts
|

From Shadow IT to Business-managed IT: a qualitative comparative analysis to determine configurations for successful management of IT by business entities

Abstract: Shadow IT describes covert/hidden IT systems that are managed by business entities themselves. Additionally, there are also overt forms in practice, so-called Businessmanaged IT, which share most of the characteristics of Shadow IT. To better understand this phenomenon, we interviewed 29 executive IT managers about positive and negative cases of Shadow IT and Business-managed IT. By applying qualitative comparative analysis (QCA), we derived four conditions that characterize these cases: Aligned, local, simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
0
10
0
6
Order By: Relevance
“…This problem is consistent with the study related to Agile budgeting [45] with a proposed model to apply multi-level budgeting where the budget could be moved between different levels. The problem of budget allocation in the context of Agile projects was also stressed in previous studies [46] where conventional management approaches and their control were not compatible with Agile ways of working. Participants suggested that with growth of the cloud, software on-line renting and different platforms, so called "shadow IT" is becoming an area where IT-related spending is not controlled by IT departments nor fully managed by business.…”
Section: Improvement Suggestionsmentioning
confidence: 97%
“…This problem is consistent with the study related to Agile budgeting [45] with a proposed model to apply multi-level budgeting where the budget could be moved between different levels. The problem of budget allocation in the context of Agile projects was also stressed in previous studies [46] where conventional management approaches and their control were not compatible with Agile ways of working. Participants suggested that with growth of the cloud, software on-line renting and different platforms, so called "shadow IT" is becoming an area where IT-related spending is not controlled by IT departments nor fully managed by business.…”
Section: Improvement Suggestionsmentioning
confidence: 97%
“…In the South African context, several social media virtual platforms are used, such as ResearchGate, Google Scholar, Facebook, Twitter, Instagram, YouTube, WhatsApp, Telegram, LinkedIn, and many others. Besides social media with the elements of entertainment, many academics prefer Wikipedia and Wikimedia, where more than 1.4 billion individuals have created OER available on these platforms ( Hilchey, 2021 ), this cannot be denied because it is still part of open access.Whereas other institutions and academics rely on shadow IT to cater to OER shadow, IT refers to ICT facilities that are not officialised by the central IT department of an organisation ( Kopper et al., 2020 ). The study on the domestication of OER by academics in a South African institution noted shadow IT as a contribution to OER practices ( Mncube, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…wenn sie nicht abgestimmt -das heißt Schatten-IT ist -und für langfristige Prozesse genutzt wird [7].…”
Section: Kerntheseunclassified
“…So sollte sich die IT-Organisation um Querschnittsfunktionen kümmern, um kontrollierte Bedingungen und Skaleneffekte zu schaffen. Dies beinhaltet beispielsweise die Bereitstellung der Infrastruktur (einschließlich Plattformen, zum Beispiel Low-Code-Plattformen), die Systemintegration (insbesondere mit den Kernsystemen), das Vertrags-und Lieferantenmanagement (zum Beispiel Cloud-Verträge), das Management der Sicherheit (Bereitstellung von Fachwissen und Überprüfung) und die Schaffung von Architekturstandards (Validierung von Systemdesigns) [7,9,10]. Fachbereiche können hingegen -im Rahmen von vorgegebenen Standards und Richtlinien -lokale Lösungen aufbauen und in multidisziplinären Teams Business-managed IT entwickeln.…”
Section: Co-governance Ist Ein Möglicher Ansatz Zur Steuerung Von Bus...unclassified
See 1 more Smart Citation